Determinant factors associated with the use of evidence‐based dietetics practice among registered dietitian nutritionists. - Van Horn, Leslie Thompson; Wright, Lauri; Arikawa, Andrea Y.; Sealey‐Potts, Claudia; Hamadi, Hanadi (Nutrition & Dietetics, 2023)
Aims: There is a lack of research assessing perceived and actual evidence‐based dietetics practice knowledge among registered dietitian nutritionists. This cross‐sectional research examined the association between determinant factors (i.e., education attainment) and objective knowledge (i.e., quiz items) of evidence‐based dietetics practices. Other determinant factors associated with perceived knowledge and skill, attitudes, behaviours and outcomes related to evidence‐based dietetics practice were also assessed. Perceived knowledge items were compared to objective knowledge items to evaluate the accuracy of self‐assessed evidence‐based dietetics practice knowledge among dietitians in the United States. Methods: A modified and adapted evidence‐based practice survey was emailed to registered dietitian nutritionists in the United States via the Commission on Dietetic Registration database between November and December 2020. Analysis of variance assessed the relationship between highest degree held and actual knowledge of evidence‐based dietetics practices. Multiple linear regression and ordinal logistic regression determined participant‐level characteristics associated with survey subscales and survey items, respectively. Pearson's correlation coefficient evaluated the relationship between subjective and objective items. Results: Four hundred and eighty‐two dietitians completed the survey. Each increase in degree type was associated with an increase in objective knowledge score (all comparisons p < 0.001). Other determinants included recency of degree completion and peer‐reviewed publications. Moderate positive associations (r = 0.35, p < 0.001) were found between subjective and objective measures. Conclusion: Graduate‐level education, recency of degree completion and peer‐reviewed publications were supportive of evidence‐based dietetics practice‐related outcomes. Future research should evaluate the efficacy of training, particularly among those further from their highest completed degree.